GASTRIC ANTRAL VASCULAR ECTASIA: CLINICAL FEATURES, ASSOCIATIONS AND PROGNOSIS. (8th June 2013) - Jalil, A; Ponichtera, J; Hameed, H; Purcell, C; Eatock, M
Abstract : Introduction: Gastric antral vascular ectasia (GAVE) is a rare disorder characterised by upper GI bleeding, chronic iron-deficiency anaemia and endoscopic findings of columns of red tortuous vessels along the longitudinal folds of the antrum of the stomach. Although the pathogenesis of this condition is largely unknown, it is associated with a number of medical conditions including portal hypertension and scleroderma. There have been few studies analysing the prevalence of the associated conditions in a cohort of GAVE cases, and none in a sample size of greater than 15. Method: This is a retrospective cohort study of all patients diagnosed with GAVE an Milton Keynes district general hospital between November 2007 and November 2012. Information was gathered from electronically stored patient records. Results: 20 patients were identified, 50% of cases were male. Average age at diagnosis overall was 65 years. The most common symptom that lead to a diagnosis of GAVE was of iron deficiency anaemia. 45% of cases had a co-existing diagnosis of liver cirrhosis (n=9), 35% chronic renal failure, 25% (n=7) had diabetes (n=5), 20% had rheumatologic disease (n=4) and in half of these the condition was scleroderma, 11% of the cohort had thyroid function abnormalities (n=2). Patients were followed up for a mean period of 1.9 years and in this period one patient had an acute GI bleed. Argon Plasma Coagulation was performed in 5 cases and the remaining cases were treated medically. Following APC the haemoglobin increased by an average of 3.75 g/dL. Conclusion: GAVE is an important differential diagnosis in the setting of iron deficiency anaemia on a background of cirrhotic liver disease or portal hypertension, especially in patients in their sixties or older. This cohort confirms the associations in previous studies but also notes that acute bleed risk is low and that APC appears an effective treatment modality.